Analisis Pengaruh Penerapan Protokol Kesehatan Dan Psikologis Terhadap Minat Berkunjung Wisatawan Ke Bali Selama Pandemi Covid-19 - Saputra, Roy; Mertha, I Wayan; Wiarti, Luh Yusni (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2022)
The world is currently faced with the problem of the spread of the Covid-19 virus. The outbreak that appeared in Wuhan, China, was first reported to WHO on December 31, 2019. The cases and victims of Covid-19 spread across various countries indicate that Covid-19 has become a global problem, and has had an impact on international activities, such as the economy and the economy. various other activities. The global COVID-19 pandemic has created new problems for nation-states, especially regarding how the state's efforts to prevent and stop the spread of this virus from spreading further. Social vaccines such as social distancing and lockdown policies are also carried out by countries in response to this emergency situation. The rapid growth of the tourism industry in Indonesia is a fairly complex challenge in providing a sense of comfort and safety for tourists. This study aims to determine the factors that influence tourist interest in traveling. In this study, the data collected was tested using Partial Least Square (PLS) on 90 respondents. The sample of this study used purposive sampling. The results obtained are that statistical data analysis shows that health protocols positively and significantly affect visiting interest. The t statistic is 3.470 > t table 1.96. In addition, p-values of 0.001 <0.05 were obtained, indicating that health protocols affect the interest of visiting tourists to Bali. The results of statistical data analysis showed that psychology affected the interest in visiting in a positive and significant way. The t statistic is 3.016 > t table 1.96. In addition, p values of 0.003 < 0.05 were obtained. So that it shows that psychology has an effect on the interest of visiting tourists to Bali.